ANALYZED TRANSMISSION POWER FLOW USING MATHLAB SOFTWARE - Rafli Ramadanu; Pristisal Wibowo; Siti Anisah (INFOKUM, 2022)
Power plants that are located far from community settlements produce their advantages and advantages for electrical energy providers. The non-strategic position makes the producers of electrical energy have to deliver electrical energy to the users or customers who use electrical energy. The power flow calculation system is used to find out how much voltage, current, real power, and reactive power are received by the receiving side. The research method used is the research data approach so that it is by the data in the field. From the results of the above calculations, it can be seen that the difference in the calculation between the MATLAB M-file and the MATLAB Simulink there is a difference in the calculation of the voltage on the bus load 2 of -0.0012 Pu. The difference in calculation data can also be seen in the slack bus which has an active power of 0.02 Pu and reactive power of 0.03 Pu. The difference in calculation data can also be seen in bus load 1 which has an active power of 5.89 Pu and reactive power of 47.29 Pu. The difference in calculation data can also be seen in bus load 2 which has an active power of 60.89 Pu and reactive power of 38.79 Pu.